Associations among quadriceps strength and rate of torque development 6 weeks post anterior cruciate ligament reconstruction and future hop and vertical jump performance: A prospective cohort study - Pua, Y.-H.; Mentiplay, B. F.; Clark, R. A.; Ho, J.-Y. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Study Design: Prospective cohort. Background: Quadriceps strength is associated with hop distance and jump height in persons who have undergone anterior cruciate ligament (ACL) reconstruction. However, it is unknown whether the ability to rapidly generate quadriceps torque in the early phase of recovery is associated with future hopping and jumping performance in this population. Objective: To evaluate the prospective associations among quadriceps strength and rate of torque development (RTD) and single-leg hop for distance, vertical jump height, vertical ground reaction force (vGRF), and vertical force loading rate during a landing task in persons who have undergone ACL reconstruction. Methods: Seventy patients with unilateral ACL reconstruction participated. At 6 weeks post ACL reconstruction, isometric quadriceps strength and RTD were measured using a dynamometer. At 6 months following ACL reconstruction, patients performed the single-leg hop for distance test. Patients also performed the single-leg vertical jump test on a force plate that measured maximum jump height, vGRF, and average loading rate during landing. Results: Both quadriceps strength and RTD at 6 weeks post ACL reconstruction were associated with all hopping and jumping measures at 6 months post ACL reconstruction (P=.04). Single-leg hop distance was associated more closely with quadriceps strength than with quadriceps RTD (P = .05), and vertical jump height and vGRF measures were associated more closely with quadriceps RTD than with quadriceps strength (P = .05 and P<.01, respectively). Both quadriceps measures were associated with loading rate. Conclusion: Quadriceps strength and RTD are complementary but distinct predictors of future hopping and jumping performance in persons who have undergone ACL reconstruction. These findings may contribute to improved rehabilitation of patients who are at risk for poor jumping/hopping performance and abnormal knee loading